2017
DOI: 10.1371/journal.pgen.1006964
|View full text |Cite
|
Sign up to set email alerts
|

rahu is a mutant allele of Dnmt3c, encoding a DNA methyltransferase homolog required for meiosis and transposon repression in the mouse male germline

Abstract: Transcriptional silencing by heritable cytosine-5 methylation is an ancient strategy to repress transposable elements. It was previously thought that mammals possess four DNA methyltransferase paralogs—Dnmt1, Dnmt3a, Dnmt3b and Dnmt3l—that establish and maintain cytosine-5 methylation. Here we identify a fifth paralog, Dnmt3c, that is essential for retrotransposon methylation and repression in the mouse male germline. From a phenotype-based forward genetics screen, we isolated a mutant mouse called ‘rahu’, whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 90 publications
1
63
0
1
Order By: Relevance
“…Dnmt3l lacks a catalytic domain, but can assist Dnmt3a and Dnmt3b. It is responsible for methylating the promoter regions of recently evolved retrotransposons in the male germline and suppresses the expression of those 'young and dangerous' transposons during early spermatogenesis, and thus is necessary for mouse fertility (Barau et al, 2016;Jain et al, 2017). Dnmt3c is a newly identified de novo methyltransferase, which seems to have arisen from a duplication event of Dnmt3b in the rodent genome, and was first annotated as a pseudogene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dnmt3l lacks a catalytic domain, but can assist Dnmt3a and Dnmt3b. It is responsible for methylating the promoter regions of recently evolved retrotransposons in the male germline and suppresses the expression of those 'young and dangerous' transposons during early spermatogenesis, and thus is necessary for mouse fertility (Barau et al, 2016;Jain et al, 2017). Dnmt3c is a newly identified de novo methyltransferase, which seems to have arisen from a duplication event of Dnmt3b in the rodent genome, and was first annotated as a pseudogene.…”
Section: Discussionmentioning
confidence: 99%
“…There are mainly three types of DNA methyltransferases in mammals, Dnmt1 (Svedruzic, 2008), Dnmt3a (Yang, Rau, & Goodell, 2015) and Dnmt3b (Duan et al, 2015). The Dnmt3 family consists of Dnmt3a, Dnmt3b, Dnmt3l and Dnmt3c (Barau et al, 2016;Jain et al, 2017), the last of which was recently discovered only in the rodent genome. Dnmt3a and Dnmt3b are well known for generating a de novo methylation pattern (Chedin, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Closer phylogenetic analyses in several taxa have revealed mammalian lineage-specific duplications, including the duplication and co-retention of several Dnmt1 paralogs in marsupials (17) and the evolution of Dnmt3L from Dnmt3A in eutherian mammals (18). Another gene duplication from Dnmt3B gave rise to Dnmt3C in muroid rodents where it has acquired a distinct, non-redundant role in retrotransposon repression during spermatogenesis (19, 20). Thus, a series of ancient and recent gene duplications have led to the current repertoires of mammalian DNMTs.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies showed that DNMT3C is the crucial enzyme for this process (19, 20). Dnmt3C knock-out (KO) males are sterile and their germ cell methylation profiles are similar to those of piRNA mutants, with a 1% drop in genome-wide DNA methylation content that selectively affects the promoters of young copies of LINE and ERVK retrotransposons (20, 23, 25).…”
Section: Introductionmentioning
confidence: 99%